PENGEMBANGAN MODEL PEMBELAJARAN MENULIS TEKS CERITA PENDEK BERBASIS PENDEKATAN METAKOGNITIF BAGI SISWA SMP - Raden Ika Mustika; Asep Ikin Sugandi (STKIP Siliwangi, 2019)
This study aims to produce a learning model for writing short story texts (short stories) based on a metacognitive approach for junior high school students. The research method used is research on the development of the Sugiyono development model. The research procedure uses the following stages: 1) potential problems, 2) collecting information and literature study, 3) product design, 4) design validation, 5). design improvements, 6) product trials, 7) product revisions, 8) usage trials, 9) product revisions, and 10) mass product manufacture. The population of this study was class VIII students of one of the junior high schools in West Bandung Regency with a purposive sample of 34 people. Research data includes test and non-test data. The results showed that the learning model for writing short stories based on a metacognitive approach was valid to be applied in learning and was proven to be effective in improving the ability to write short stories for junior high school students.